The USA patriot act - Gronbeck, Bruce E. (Javnost (Ljubljana), 2004)
Domestic and international issues of the 1990s form an incendiary combination of controversies that heightened American fears, anger, and sensitivity to thepolitics of difference and provide the background for the passing of the Patriot Act of 2001. The author argues that censorship occurs with the silencing of voices in a democracy and describes the control of voice in the post-USA Patriot Act era, where the danger of censorial power resides in secrecy combined with indeterminacy.
Keywords: United States of America; ZDA; state; država; authority; oblast; democracy; demokracija; svoboda; informiranje; javno obveščanje; nadzor; cenzura